The circumstance of anemia possessed in Japanese athletes: In case of 1998 national sports festival - Toba, Y.; Sakamoto, S.; Kawahara, T.; Fukubayashi, T.; Nakajima, H. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The purpose of this research was to investigate and analyse the state of Anemia possessed in Japanese Athletes.